The experience sampling method as an mHealth tool to support self‐monitoring, self‐insight, and personalized health care in clinical practice. Issue 6 (23rd May 2017) - van Os, Jim; Verhagen, Simone; Marsman, Anne; Peeters, Frenk; Bak, Maarten; Marcelis, Machteld; Drukker, Marjan; Reininghaus, Ulrich; Jacobs, Nele; Lataster, Tineke; Simons, Claudia; et al.
Abstract : Background: The experience sampling method (ESM) builds an intensive time series of experiences and contexts in the flow of daily life, typically consisting of around 70 reports, collected at 8–10 random time points per day over a period of up to 10 days. Methods: With the advent of widespread smartphone use, ESM can be used in routine clinical practice. Multiple examples of ESM data collections across different patient groups and settings are shown and discussed, varying from an ESM evaluation of a 6‐week randomized trial of mindfulness, to a twin study on emotion dynamics in daily life. Results: Research shows that ESM‐based self‐monitoring and feedback can enhance resilience by strengthening the capacity to use natural rewards. Personalized trajectories of starting or stopping medication can be more easily initiated and predicted if sensitive feedback data are available in real time. In addition, personalized trajectories of symptoms, cognitive abilities, symptoms impacting on other symptoms, the capacity of the dynamic system of mental health to "bounce back" from disturbance, and patterns of environmental reactivity yield uniquely personal data to support shared decision making and prediction in clinical practice. Finally, ESM makes it possible to develop insight into previous implicit patterns of thought, experience, and behavior, particularly if rapid personalized feedback is available. Conclusions: ESM enhances clinical practice and research. It is empowering, providing co‐ownership of the process of diagnosis, treatment evaluation, and routine outcome measurement. Blended care, based on a mix of face‐to‐face and ESM‐based outside‐the‐office treatment, may reduce costs and improve outcomes.